THE EFFECT OF PROFITABILITY, LEVERAGE, AND SALES VOLATILITY ON TAX AVOIDANCE WITH INSTITUTIONAL OWNERSHIP AS A MODERATING VARIABLE: AN EMPIRICAL STUDY ON PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2021–2024 PERIOD - Putri Ellie Rahmawati; I Ketut Sujana (ADISAM Publisher, 2025)
Tax avoidance practices in the property and real estate sector have drawn attention due to the sector’s capital-intensive nature, long-term business cycles, and high flexibility in revenue recognition. These characteristics provide managerial discretion in fiscal decision-making, particularly when facing post-pandemic liquidity pressures. The gap between accounting profits and payable taxes observed in several companies within this sector further indicates potential tax avoidance. This study aims to examine the effect of profitability, leverage, and sales volatility on tax avoidance, with institutional ownership as a moderating variable. The research employs a quantitative approach using purposive sampling on 17 property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2024 period, resulting in 68 observations. Data analysis was conducted using Moderated Regression Analysis (MRA) with the assistance of SPSS version 26. The results reveal that profitability has a significant negative effect on tax avoidance, while leverage has a significant positive effect. Sales volatility shows no significant effect on tax avoidance. Furthermore, institutional ownership weakens the positive effect of leverage on tax avoidance but does not moderate the relationship between profitability or sales volatility and tax avoidance. These findings contribute to the agency theory literature and provide practical insights for regulators in strengthening fiscal oversight in the property and real estate sector.